2017
DOI: 10.1111/cdoe.12283
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride in the diet of 2‐years‐old children

Abstract: The fluoride concentrations of foods and beverages vary widely, and, if items in the 95th percentile of fluoride intake distribution are ingested, children could consume more fluoride than the recommended 0.05 mg/kg/d. Fluoride intake calculated in this study was higher than historically reported dietary levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Results indicate a hypercaloric and hyperproteic diet as the most frequent, which is related to the diet of the evaluated provinces (27), where fluorosis occurred in different degrees (28), with specific clinical manifestations (25). High levels of fluoride were not observed, which could be considered beneficial to the teeth (28); however, it is necessary to perform control processes of the composition of certain foods (24), as well as the involuntary intake of hygiene products (26), which could be related to the presence of the detected fluorosis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Results indicate a hypercaloric and hyperproteic diet as the most frequent, which is related to the diet of the evaluated provinces (27), where fluorosis occurred in different degrees (28), with specific clinical manifestations (25). High levels of fluoride were not observed, which could be considered beneficial to the teeth (28); however, it is necessary to perform control processes of the composition of certain foods (24), as well as the involuntary intake of hygiene products (26), which could be related to the presence of the detected fluorosis.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding appropriate oral hygiene habits, one of the most important to maintain oral health is tooth brushing plus toothpaste; however, it could be the most determinant cause of the presence of fluorosis (26), as detected in the study, especially considering the fact that children started brushing their teeth with fluoride toothpaste for adults. 1450 mg / L of fluoride (27), with unmonitored and unregulated amount of toothpaste (11,23), is reflected in the correlation value of 0.162 detected, especially when considering that toothpastes marketed in the Ecuador have a percentage of fluorine that exceeds 1000 ppm which is beneficial from the preventive and protective point of view; however, it would be worth analyzing the amount used to confirm this association with the fluorosis detected.…”
Section: Discussionmentioning
confidence: 99%
“…The wide range of F content within food and beverage groups verified in the UK fluoride database [ 34 ], in several Brazilian studies [ 20 , 24 , 25 , 26 , 27 ] and in a recent study in the US [ 21 ] accentuates the need for comprehensive F labeling of foods and beverages, especially those that are frequently consumed by infants and young children. Monitoring F intake can be challenging and labor-intensive, requiring the assessment of F ingestion from both diet and toothpaste.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have indicated changes in children’s eating patterns over the last three decades [ 3 , 20 ]. This may have been attributed to the consumption of different types of food, perhaps due to more industrialized options, as well as to different methods of analyzing the F that is present in the products that are more commonly available in the market [ 21 , 22 ]. Currently, it is observed that in different age groups, children are exposed to distinct sources of F, but there are only a few studies that report the risk-benefit relationship of F intake through consumption of foods and beverages [ 9 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…58,239,240 The cases reported include also more cases of moderate-to-severe fluorosis. 58,[239][240][241] One of the possible reasons might be that fluoride appears to be more readily available for consumption nowadays during the critical window when enamel is most susceptible to fluorosis. 240…”
Section: Fluoride Intake In Childrenmentioning
confidence: 99%